Active Tension Control for WT Wheelchair Robot by Using a Novel Control Law for Holonomic or Nonholonomic Systems. (2nd October 2013) - Wang, Jian; Wang, Ting; Yao, Chen; Li, Xiaofan; Wu, Chengdong
Abstract : Interactional characteristics between WT wheelchair robot and stair environment are analyzed, and possible patterns of WT wheelchair robot during the stair-climbing process are summarized, with the criteria of the wheelchair robot for determining the pattern proposed. Aiming at WT wheelchair robot's complicated mechanism with holonomic constraints and combined with the computed torque method, a novel control law that is called active tension control is presented for holonomic or nonholonomic robotic systems, by which the wheelchair robot with a holonomic or nonholonomic mechanism can track the reference input of the constraint forces of holonomic or nonholonomic constraints as well as tracking the reference input of the generalized coordinate of each joint. A stateflow module of Matlab is used to simulate the entire stair-climbing process for WT wheelchair robot. A comparison of output curve with the reference input curve of each joint is made, with the effectiveness of the presented control law verified.